2016
DOI: 10.1074/mcp.m115.051318
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Hippocampal Protein Expression During Long-term Spatial Memory Formation

Abstract: Spatial memory depends on the hippocampus, which is particularly vulnerable to aging. This vulnerability has implications for the impairment of navigation capacities in older people, who may show a marked drop in performance of spatial tasks with advancing age. Contemporary understanding of long-term memory formation relies on molecular mechanisms underlying long-term synaptic plasticity. With memory acquisition, activity-dependent changes occurring in synapses initiate multiple signal transduction pathways en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 136 publications
1
9
0
Order By: Relevance
“…Few studies have looked at memory-dependent changes in protein expression in the hippocampus, and ours is notable because it describes CA1-and CA3-specific effects in detail. A recent report examined protein expression changes in the whole hippocampus following a spatial memory task (radial arm maze) over multiple days (Borovok et al, 2016), and it iden-tified proteins with altered expression during the memory acquisition phase (day 1), the steep learning improvement phase (day 3), and the final curve of the learning phase (day 5). While yielding interesting results, including changes in proteins associated with mitochondrial metabolism activity, this study analyzed protein expression following multiple consecutive learning experiences, and it used naive home cage mice as a control group, making it impossible to distinguish between learning-induced effects and effects induced by exploration and increased activity.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have looked at memory-dependent changes in protein expression in the hippocampus, and ours is notable because it describes CA1-and CA3-specific effects in detail. A recent report examined protein expression changes in the whole hippocampus following a spatial memory task (radial arm maze) over multiple days (Borovok et al, 2016), and it iden-tified proteins with altered expression during the memory acquisition phase (day 1), the steep learning improvement phase (day 3), and the final curve of the learning phase (day 5). While yielding interesting results, including changes in proteins associated with mitochondrial metabolism activity, this study analyzed protein expression following multiple consecutive learning experiences, and it used naive home cage mice as a control group, making it impossible to distinguish between learning-induced effects and effects induced by exploration and increased activity.…”
Section: Discussionmentioning
confidence: 99%
“…Fig2.1E), we chose to use cell-type-specific NCAA labelling in RC3xCamk2a-Cre mice to examine de novo protein synthesis in hippocampal neurons in vivo.Combining hippocampal neuron-specific ANL labelling with BONCAT-SWATH-MS, we identified 156 proteins which were significantly altered in synthesis during spatial LTM formation induced by the 30 min APA paradigm (Fig2.3A). While these changes represent a small proportion of the total de novo proteome, these findings are in line with previous studies assessing the total proteome in different stages of memory consolidation(Borovok et al, 2016). STRING analysis of the 156 significantly altered proteins revealed that the vast majority of these proteins interact with a least one other significantly altered protein, forming a large, highly interconnected network (Fig2.4).…”
supporting
confidence: 90%
“…Our approach allowed to compare protein expression profiles as a property of dominant and submissive relationship resembling important elements of manic and depressive‐like behavior, respectively , and social interaction. Application of explorative factor analysis to strikingly complex data of neural system proteomics, as previously , (Suppl. Fig.…”
Section: Discussionmentioning
confidence: 99%